Pengaruh Metode Write Around Terhadap Keterampilan Menulis Teks Anekdot Siswa Kelas X SMAN 1 Lengayang - Nur Azizah; Ricci Gemarni Tatalia; Ria Satini (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2023)
This research is motivated by the problem that students are not yet skilled at writing anecdotal texts. As well as the lack of an interesting learning model, which makes it difficult for students to understand and write anecdotal texts. This study aims to describe the effect of the write around method on the anecdotal text writing skills of class X students of SMAN 1 Lengayang. This type of research is quantitative research after using the experimental learning model. The design of this research is One Group Pretest-Posttest Design. The population of this research is all students of class X SMAN 1 Lengayang. The sample in this study were 32 class X students of SMAN 1 Lengayang. The data in this study were the scores of anecdotal text writing skills before and after using the write around model for class X SMA 1 Lengayang. The results of this study can be concluded as follows. First, the level of ability to write anecdotal texts for class X students of SMA Negeri 1 Lengayang before using the Write Around learning method obtained an average score of 57.44 with a classification of 56-65%, namely moderate (S). Second, the ability level of anecdotal text writing skills for class X students of SMA Negeri 1 Lengayang using the Write Around learning method obtained an average score of 67.47 with a classification of 66-75%, which is enough (C). Third, based on the results of the t-test it was concluded that there was an effect of using the Write Around learning method on the ability to write anecdotal text skills in class X SMA Negeri 1 Lengayang because tcount > t_table 6.64 > 1.66 So, it can be concluded that the ability to write anecdotal texts class X SMA Negeri 1 Lengayang using the Write Around method is better than before using the Write Around method.